Epitopes of Immunoreactive Proteins of Streptococcus Agalactiae: Enolase, Inosine 5′-Monophosphate Dehydrogenase and Molecular Chaperone GroEL - Dobrut, Anna; Brzozowska, Ewa; Górska, Sabina; Pyclik, Marcelina; Gamian, Andrzej; Bulanda, Małgorzata; Majewska, Elzbieta; Brzychczy-Włoch, Monika (Frontiers in Cellular and Infection Microbiology, 2018)
Three Streptococcus agalactiae (group B streptococci, GBS) immunoreactive proteins: enolase (47.4 kDa), inosine 5′-monophosphate dehydrogenase (IMPDH) (53 kDa) and molecular chaperone GroEL (57 kDa) were subjected to investigation. Enolase protein was described in our previous paper, whereas IMPDH and GroEL were presented for the first time. The aim of our paper was to provide mapping of specific epitopes, highly reactive with umbilical cord blood serum. Bioinformatic analyses allowed to select 32 most likely epitopes for enolase, 36 peptides for IMPDH and 41 immunoreactive peptides for molecular chaperone GroEL, which were synthesized by PEPSCAN. Ten peptides: two in enolase, one in IMPDH and seven in molecular chaperone GroEL have been identified as potentially highly selective epitopes that can be used as markers in rapid immunological diagnostic tests or constitute a component of an innovative vaccine against GBS infections.